2009
DOI: 10.1016/j.jnucmat.2009.01.257
|View full text |Cite
|
Sign up to set email alerts
|

An overview of a comprehensive First Mirror Test for ITER at JET

Abstract: a b s t r a c tThe test was performed with 32 stainless steel and molybdenum mirrors placed in pan-pipe shaped cassettes and exposed in JET in the divertor and on the main chamber wall for 127 000 s including 97 000 s of X-point operation. Surface composition and total reflectivity were determined afterwards. All mirrors from the divertor were coated with deuterated carbon deposits causing the reflectivity loss by a factor of 6-10 in the visible range. Flaking and exfoliation of deposits were observed in some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 11 publications
5
26
1
1
Order By: Relevance
“…Therefore, the main effort should be concentrated on the development of methods for in-situ cleaning and/or protection of mirrors in a reactor-class device. Several options for deposit removal have been critically assessed earlier [3] and photonic cleaning has been recently tested on the JET mirrors [6]. It has shown that photonic methods inside the diagnostic channels may be ineffective or even damage the mirrors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the main effort should be concentrated on the development of methods for in-situ cleaning and/or protection of mirrors in a reactor-class device. Several options for deposit removal have been critically assessed earlier [3] and photonic cleaning has been recently tested on the JET mirrors [6]. It has shown that photonic methods inside the diagnostic channels may be ineffective or even damage the mirrors.…”
Section: Discussionmentioning
confidence: 99%
“…The entire research program comprises: (a) the selection of material for test mirror, (b) manufacture of mirrors and their carriers for in-vessel installation, (c) optical pre-characterisation, (d) exposure in the plasma boundary of JET for a complete operational campaign, (e) a broad range of post-exposure analyses by means of optical and surface analysis method, (f) correlation with erosion-deposition pattern measured by other wall diagnostics used in Tritium Retention Studies (TRS) [5] and (g) photonic cleaning of the exposed mirrors [6] followed by the analyses of cleaned surfaces and examination of products generated by the laser light impact. The change of optical properties of mirrors retrieved from the vessel after the experimental campaigns in [2005][2006][2007] has been discussed earlier [3]. The essential result is that the reflectivity of all tested mirrors was significantly degraded either by erosion with charge exchange neutrals or by the formation of thick deposits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two campaigns in JET with carbon walls have been performed. The changes in optical properties of mirrors retrieved from the vessel after the first campaign (2005)(2006)(2007) have been discussed earlier [2]. The aim of the present work is to provide an overview of the results obtained during the second round of the test and, based on the outcome of the two campaigns, to discuss options for mirror maintenance and cleaning in a steady-state reactor.…”
Section: Introductionmentioning
confidence: 92%
“…One has to recognize and assess the impact of the long-term exposure in a tokamak on the reflectivity change. Therefore, on the request of the ITER design team, the first mirror test (FMT) has been carried out at JET [1,2]. The entire research program comprises: (a) selection of material for the test mirror, (b) manufacture of mirrors and their carriers (cassettes of pan-pipe shape) for in-vessel installation, (c) optical pre-characterization of mirrors, (d) exposure in the plasma boundary of JET during a complete operational campaign, (e) a broad range of post-exposure analyses by means of optical and surface analysis methods, (f) analyses of deposition in the channels of the mirror carriers [3] and (g) photonic cleaning of the exposed mirrors [4], followed by analyses of cleaned surfaces and examination of products generated by the laser light impact.…”
Section: Introductionmentioning
confidence: 99%